Digital transformations of illicit drug markets : reconfiguration and continuity - Tzanetakis, Meropi; South, Nigel (Bingley, U.K. : Emerald Publishing Limited, 2023)
The ebook edition of this title is Open Access and freely available to read online. Transnational illicit markets have been transformed by the digital revolution. They take advantage of encryption technologies, smartphones, social media applications and cryptocurrencies that protect the digital traces of buyers and sellers, posing new challenges to drug control policies and public health alike. Digital Transformations of Illicit Drug Markets: Reconfiguration and Continuity considers how the digital revolution has changed the selling and buying of illicit substances through increased convenience and anonymisation. Providing a uniquely interdisciplinary perspective, chapters show how the digital transformation of illicit drug markets combines a reconfiguration of how sellers and buyers interact in new markets. Emphasising that illicit digital markets are embedded in societal structures and power relations in general, contributors also recognise the importance of critical perspectives on inequalities between the Global North and South as well as issues of gender. Digital Transformations of Illicit Drug Markets: Reconfiguration and Continuity challenges the field of criminology to recognise the limits of its traditional knowledge and move beyond the preoccupations that restrict crime to certain fixed spaces in order to develop new explanations.
Chapter 1. Introduction: The digital transformations of illicit drug markets as a process of reconfiguration and continuity / Meropi Tzanetakis and Nigel South -- Part I: Embeddedness of digital drug markets -- Chapter 2. Social media applications and 'surface web' mediated supply of illicit drugs: Emergent and established market risks and contradictions / Ross Coomber, Andrew Childs, Leah Moyle, and Monica Barratt -- Chapter 3. Trust in cryptomarkets for illicit drugs / Kim Moeller -- Chapter 4. Drugs and the dark web: The Americanisation of policing and online criminal law from an australian perspective / Ian J. Warren and Emma Ryan -- Part II: Understanding drug demand online -- Chapter 5. 'Waiting for the delivery man': Temporalities of addiction, withdrawal, and the pleasures of drug time in a darknet cryptomarket / Angus Bancroft -- Chapter 6. When home delivery trumps a shady warehouse deal. An exploratory study of belgian cryptomarket buyers' profile and their motives to buy online / Charlotte Colman -- Part III: Power relations -- Chapter 7. Cultural politics, reciprocal relations, and operational agility in online drug markets / Nicolae Craciunescu and Nigel South -- Chapter 8. Gender representations in online modafinil markets / Jennifer Fleetwood and Caroline Chatwin -- Chapter 9. Cryptomarkets and drug market gentrification / James Martin -- Chapter 10. The dark side of cryptomarkets: Towards a new dialectic of self-exploitation within platform capitalism / Meropi Tzanetakis and Stefan A. Marx.
Includes bibliographical references and index.
Print version record.
Keywords: Drug traffic -- Technological innovations; Black market; Computer crimes; Electronic commerce; Social Science -- Criminology; Drugs trade, drug trafficking